Voxel-Based Morphometry Reveals a Correlation Between Bone Mineral Density Loss and Reduced Cortical Gray Matter Volume in Alzheimer’s Disease - Takano, Yumi; Tatewaki, Yasuko; Mutoh, Tatsushi; Morota, Naoya; Matsudaira, Izumi; Thyreau, Benjamin; Nagasaka, Tatsuo; Odagiri, Hayato; Arai, Hiroyuki; Taki, Yasuyuki (Frontiers in Aging Neuroscience, 2020)
Background: Decreased bone mineral density (BMD) was associated with poorer cognitive function and increased risk of Alzheimer’s disease (AD). However, objective evidence for the relationship between osteoporosis and AD in humans has not been extensively described. Objectives: We aimed to evaluate the relationships between BMD and the cortical volumes of brain regions vulnerable to AD; hippocampus, parahippocampal gyrus, precuneus, posterior cingulate, and angular gyrus, using voxel-based morphometry, in order to investigate the association between bone loss and AD. Methods: A cohort of 149 consecutive elderly participants who complained of memory disturbance underwent high-resolution structural brain MRI and dual energy X-ray absorptiometry. We used SPM12 software to conduct a voxel-based multiple regression analysis to examine the association between femoral neck BMD values and regional grey matter volume (rGMV) on structural T1-weighted MRI. Results: After adjusting for subject age, gender, total brain volume, and mini-mental state examination scores, the multiple regression analysis showed significant correlations between BMD loss and rGMV decline in the left precuneus, which is an important neural network hub vulnerable to AD. Conclusion: These data suggest that the bone and brain communicate with each other, as in “bone-brain crosstalk”, and that control of BMD factors could contribute to cognitive function and help prevent AD.